EDUCATIVE COMMUNICATION ETHICS IN THE FAMILY TOWARD MUSLIM STUDENT RELIGIOSITY - Arro'uf, Khofifah; Rahmat, Munawar; Suresman, Edi (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
The purpose of this research was to find out the ethics of educative communication in the family on the religiosity of Muslim students. To describe the problem, quantitative research was conducted with correlational methods that seek the relationship or influence between educative communication ethics in the family on the religiosity of Muslim students. The total research population was 131 with a sample of 100 respondents. Inventory of educative communication ethics 26 items and religiosity of Muslim students 22 items were submitted to them. After analyzing and interpreting the results of the correlation test using the product moment (person) correlation test and regression test with a simple regression model. The results of this study indicate that the correlation test can be known that there is a positive relationship between educative communication ethics in the family on the religiosity of Muslim students. The value of early communication ethics in the family (X) on the religiosity of Muslim students (Y) is 0.259. The variable of educative communication ethics in the family has a significant influence on religious behavior with a significant value of 0.01 <0.25 and the value of t count 3.360 > t table 1.987. It can be concluded that there is an influence between educative communication ethics on the religiosity of Muslim students.